1992
DOI: 10.2307/2061360
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment and providing child care

Abstract: This paper considers self-employment and providing child care as occupational strategies that can lower the cost of child care. If the ability to care for one's own children while engaged in market work is important to mothers with young children, we predict that women with young children will be more likely to choose to be self-employed or to be a child care provider than women without young children. The analysis provides strong support for this hypothesis. The results show that the presence of young childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 18 publications
6
76
1
10
Order By: Relevance
“…Moreover, sole parents also have more equity in businesses than equally wealthy single individuals without children at home. This is consistent with previous evidence that the number of children at home is positively related to the probability that a women is self-employed (Connelly 1992 …”
Section: Asset Portfoliossupporting
confidence: 93%
“…Moreover, sole parents also have more equity in businesses than equally wealthy single individuals without children at home. This is consistent with previous evidence that the number of children at home is positively related to the probability that a women is self-employed (Connelly 1992 …”
Section: Asset Portfoliossupporting
confidence: 93%
“…These studies demonstrate the blurring of boundaries between the notions of 'choice' and 'constraint', which is contrary to the approach made in standard choice theoretic occupational choice models such as those by Marcoullier et al (1997) and Maloney (1999) emphasize. The study by Connelly (1992), for example, makes use of US panel data to demonstrate that women with young children are more likely to choose to be self-employed or to be a child care provider than women without children. 5 Given the nature of constraint that young children place on women's employment, "the simple choice between being employed and not being employed may mask important aspects of the decision regarding participation."…”
Section: Considerationsmentioning
confidence: 99%
“…Recent fertility research suggests that self-employed people should be treated as a distinct group. The incidence of childlessness is low amongst self-employed women because the flexibility of self-employment makes it easier to reconcile family and work obligations (Boden 1999;Connelly 1992;Köppen, Mazuy, and Toulemon 2017). In the case of men, previous research has consistently shown that socioeconomically disadvantaged men, such as the unemployed or those in low-paid jobs, are the most likely to remain childless (Berrington 2017;Keizer, Dykstra, and Poortman 2010;Parr 2010), whilst self-employed men are the least likely (Köppen, Mazuy, and Toulemon 2017).…”
Section: Reasons For Childlessnessmentioning
confidence: 99%